PETROLEUM SYSTEMS IN THE RIONI AND KURA BASINS OF GEORGIA. (26th June 2021) - Sachsenhofer, R. F.; Bechtel, A.; Gratzer, R.; Enukidze, O.; Janiashvili, A.; Nachtmann, W.; Sanishvili, A.; Tevzadze, N.; Yukler, M. A.
Abstract : The Neogene Rioni and Kura foreland basins in Georgia are located between the converging Greater and Lesser Caucasus fold‐and‐thrust belts. The Rioni Basin continues westward into the Black Sea whereas the Kura Basin extends eastward into Azerbaijan and the Caspian Sea. "Pre‐" and "post‐salt" petroleum systems are distinguished in the Rioni Basin separated by an Upper Jurassic evaporite succession of regional extent. The pre‐salt petroleum system in the northern Rioni Basin is still poorly understood. Bathonian shales have generated oil which has been recorded in Middle Jurassic sandstones. However, as the origin of the oil in Upper Jurassic sandstones (e.g. at the Okumi oil discovery) is still problematic, the pre‐salt petroleum system remains poorly constrained. Gas‐rich, high volatile bituminous coals of Bathonian age may represent a CBM play. The post‐salt petroleum system in the Rioni Basin is charged by two prolific source rock units: the Middle Eocene Kuma Formation and the Oligo‐Miocene Maikop Group. The petroleum potential of the Kuma Formation, which is about 40 m thick, is classified as good to very good. The Oligocene part of the Maikop Group is several hundred metres thick and contains source rocks with up to 5 wt.% TOC in its lower part. Additional source rocks are present in Cretaceous and lower Paleogene levels. Oil is produced from fractured Upper Cretaceous carbonates in anticlinal structures below the Neogene unconformity and from Mio‐Pliocene siliciclastics in fault‐related anticlines. Trap formation and hydrocarbon accumulation is interpreted to have occurred since Maeotian time. Proven oil reserves are very low (∼2 million tons) and suggest low charge efficiency. Several stratigraphic horizons containing potential source rocks are present in the Kura Basin of eastern Georgia. Although oil‐source correlations have yielded unsatisfactory results, the Maikop Group is the most likely source rock, despite its relatively poor petroleum potential which is at best "fair" in the Tbilisi area in the west of the basin. Additional potential source rocks include Middle and Upper Eocene shales. Fractured Middle Eocene volcaniclastic rocks are the best producing reservoirs for hydrocarbons, but oil accumulations are also found in fractured Upper Cretaceous carbonates and in Lower and Upper Eocene, Oligocene and Neogene siliciclastics. Biomarker data suggest a Cenozoic (or Upper Cretaceous) source rock containing abundant terrigenous organic matter. Anticlines and positive flower structures related to compressional tectonics in front of the Greater and Lesser Caucasus fold‐and‐thrust belts form the main trap types. Samgori‐Patardzeuli‐Ninotsminda in the Tbilisi region is by far the largest oil field in Georgia and accounts for nearly 90% of the cumulative production of the country (28.5 million tons). The field was probably charged from a kitchen area located to the north. Strike‐slip faults played a major role as migration pathways. Despite of the presence of many oil seeps, proven reserves in the Georgian part of the Kura Basin are very low (2.4 million tons). This may reflects the presence of traps with poor seal integrity.